New Test Bed for Corroded Large Size Bolted Connections Under Fatigue and Pretension. Issue 4 (14th September 2022) - Betz, Kai Stephan; Schaumann, Peter; Kulikowski, Jan
Abstract: In this paper, a newly developed test method to evaluate the influence of corrosion on pretension and fatigue of bolted connections is presented, suitable from size M36 to M72. A first preliminary series of M30 property class 10.9 bolts were tested to validate the individual test setup steps and to detect challenges and improvement. Pretension load tests, static load tests and fatigue load tests were performed while monitoring stresses on a small number of bolts. The method presented is used to compare different coatings for bolts, like Hot‐dip galvanized coatings and zinc flake coatings, as well as nano‐coatings. To create a realistic approach on offshore corrosion and loading conditions, the bolts will be preloaded in a clamping device resembling the ring flange of an offshore wind tower segment. In a next step, the bolts are corroded in a climate chamber, using the salt spray test or condensation test. Following the corrosion process, the bolts are tested for fatigue without loosening the nut and damaging the thread. Before corrosion and after the fatigue test, 3D surface scans are made to document the corrosion process and to create numerical models of the corroded surface. The method presented offers a new way to evaluate fatigue, pretension and corrosion effects, which is validated on bolts M30 property class 10.9. In close future, the test method is used for larger series of corroded M36 property class 10.9 bolts, having different coating systems applied.